Molecular mechanisms of amyloid inhibition: an NMR-driven framework with polyphenols as a case study - Zuccon, Giacomo; Darnal, Aakriti; Longo, Edoardo; D’Aronco, Sara; Boselli, Emanuele; Orlando, Patrick; Ceccon, Alberto (Frontiers in Molecular Biosciences, 2025)
Misfolding and aggregation of intrinsically disordered proteins into amyloid fibrils are central to neurodegenerative diseases such as Parkinson’s, Alzheimer’s, and Huntington’s. Increasing evidence suggests that transient, low-populated oligomeric intermediates, rather than mature fibrils, are key cytotoxic species. Natural polyphenols have shown promise as amyloid inhibitors, though their mechanisms of action remain unclear due to the complexity of early aggregation. This perspective explores how solution-state NMR can quantitatively assess inhibitor mechanisms. Building on recent literature elucidating the aggregation mechanisms of the huntingtin exon 1 protein (httex1), responsible for Huntington’s disease, we propose a kinetic framework that integrates early reversible oligomerization with downstream fibril formation and models the impact of small-molecule binding at distinct stages of the pathway. We show that monomer sequestration and inhibition of elongation-competent nuclei produce distinct aggregation profiles, resolvable through global fitting of NMR and kinetic data. This mechanistic insight enables classification of inhibitors by target stage—monomeric, oligomeric, or fibrillar—and demonstrates how polyphenols serve as a biologically relevant case study for applying this general NMR-driven framework to the design of small-molecule amyloid inhibitors.